A world-class education : learning from international models of excellence and innovation - Stewart, Vivien (ASCD, 2012)
Designed to promote conversation about how to educate students for a rapidly changing, innovation-based world, this comprehensive and illuminating book from international education expert Vivien Stewart focuses on understanding what the world's best school systems are doing right for the purpose of identifying what U.S. schools-at the national, state, and local level-might do differently and better.